Begin Again: Hysteria as Forgetting, Repetition, and Atonement - Jamieson Webster (EJP import test, 2015)
Summary: What do we learn as analysts from the hysteric’s narrative style? Open, fragmented, something insisting as it circles a hole in memory or affect, a sometimes stubborn refusal to close, a multiplicity of positions occupied; these characteristics that immediately become apparent to the analyst when listening to the hysteric might embody an ideal of analytic listening, analytic discourse, and even analytic writing. Using the work of Serge Leclaire, several case examples, and a theoretical investigation of forgetting, repetition, and atonement, the author tries to show the importance of hysteria for rethinking not only how we work with hysteria clinically, but an ethic that the author calls, “always beginning again” that mirrors the difficult position of what it means to be and continue to be a psychoanalyst.
Keywords: amnesia; hysteria; jouissance; Repetition; Technique